Medication therapy of allergic rhinitis in children - D. A. Tulupov (Медицинский совет, 2015)
Allergic rhinitis is a widespread chronic pathology of the upper respiratory tract in children and adults. In a number of countries, more than 50% of the population have clinical manifestations of allergic rhinitis. [1] According to Russian authors, the prevalence of allergic rhinitis in Russia in different regions varies between 10-40% of the pediatric population [2]. Moreover, according to the latest projections, if the trend for annual growth of allergic rhinitis in Europe persists, one child who does not have allergic rhinitis will account for 3 children with allergic rhinitis. [3]